Rheological studies of ABS reinforced carbon black blends: article - Muhammad Shazwan, Harris Shazlan; Mohd Alauddin, Sakinah (2019)
Nowadays, effort of combining conductive fillers into ABS making the blends antistatic has utilized plenty of potential applications with high demand on conductive polymer composite, which are not limited to electrical insulating materials any more. Carbon black (CB) is conductive fillers that can be added into ABS. The effects of added carbon black on the processability of AcrylonitrileButadiene–Styrene (ABS) thermoplastic polymers have was been investigated. Adding carbon black with ABS has been done by changing the weight percent which range from 10% to 50% and later analyisis the trends. The flow properties of composite materials have been evaluated by Melt Flow Index. The rheological properties was calculated by result of Melt Flow Index. The processing flow decreases as the carbon black content increases. Next, the rheological properties of ABS reinforced carbon black blends has shown that flow rate in a polymer is related inversely to viscosity. High carbon black content in ABS will increases the resistance to flow. Thus will slow the flow rates.